Specific modification and self-transport of porphyrins and their multi-mechanism cooperative antitumor studies. Issue 14 (23rd March 2021) - Jia, Shuxin; Wang, Shaochen; Li, Shanshan; Hu, Peng; Yu, Shuling; Shi, Jiahua; Yuan, Jintao
Abstract : The introduction of TPGS increases the cellular uptake and antitumor activity of TAPP-TPGS. TAPP-TPGS/PTX with small size increases the enrichment of drug and photosensitizer in tumor region and has excellent biocompatibility and synergistic treatment effect of TPGS, chemotherapy and PDT. Abstract : In order to reduce the toxicity and side effects of anti-tumor drugs and improve their therapeutic effect against cancer, photodynamic and chemical combination therapy has been exploited. However, the complicated preparation and metabolic toxicity of photosensitizer-loaded materials remain major obstacles for bioapplications. In this study, we designed and prepared a specific photosensitizer self-transporting drug-delivery system. First, 5, 10, 15, 20-tetrakis(4-aminophenyl)-21 H, 23 H -porphine (TAPP) was modified using specific molecules of d -α-tocopheryl polyethylene glycol 1000 succinate (TPGS) with a certain antitumor effect, to prepare a specific fluorescent amphiphilic system (TAPP-TPGS). Then, the drug-loaded fluorescence nanomicelle (TAPP-TPGS/PTX) was formed via self-assembly using the amphiphilic system and the anticancer drug paclitaxel (PTX). The carrier material could be used as a drug tracer and cancer therapy reagent to synergistically trace the chemotherapy drug and treat cancers. The biocompatibility and the enhanced antitumor effect of TAPP-TPGS/PTX were confirmed by in vitro and in vivo experiments. To detect the synergistic anticancer effect enhanced by TPGS, TAPP-mPEG synthesized with a similar method as TAPP-TPGS was used for a comparative analysis. The results showed that the excellent synergistic anticancer effect of the TAPP-TPGS/PTX was enhanced due to the introduction of TPGS. Thus, the specific porphyrin self-transporting nanomicelle is a very promising carrier material for applications in biomedicine.